Small Municipalities and Planning: Dilemmas and Perspectives - Marquez, Gabriel; Filippim, Eliane Salete; Lazzarotti, Fábio; Fischer, Augusto (REBRAE, 2015)
The paper aims to understand the experience in preparing a training strategy linked to knowledge management, learning and organizational change done at a private institution of higher education. More specifically, it seeks to detail the stages of development, analyzing the difficulties faced and provide indicators of change throughout the process. A feature of the strategic process in the researched organization led the search for a theoretical discussion could involve strategy, knowledge and change. This association was fully viable when considering events that are mobilized by people interacting in a defined context. It uses a methodology of action research in which the investigative process includes a cycle of planning, action, observation and reflection. As a result, we defined four general indicators of the actions and influencers nine indicators of knowledge management should be promoted in the strategic process.